Spectral phase measurement of a Fano resonance using tunable attosecond pulses - M. Kotur (Nature Portfolio, 2016)
Resonant absorption of light in atoms can lead to autoionization, whose probability exhibits a Fano intensity profile. Here, the authors use attosecond pulses and weak infrared radiation to study the phase variation of the photoionization amplitude across an autoionization resonance in argon.